The TYK2-P1104A Autoimmune Protective Variant Limits Coordinate Signals Required to Generate Specialized T Cell Subsets - Gorman, Jacquelyn A.; Hundhausen, Christian; Kinsman, Mackenzie; Arkatkar, Tanvi; Allenspach, Eric J.; Clough, Courtnee; West, Samuel E.; Thomas, Kerri; Eken, Ahmet; Khim, Socheath; Hale, Malika; Oukka, Mohamed; et al. (Frontiers in Immunology, 2019)
TYK2 is a JAK family member that functions downstream of multiple cytokine receptors. Genome wide association studies have linked a SNP (rs34536443) within TYK2 encoding a Proline to Alanine substitution at amino acid 1104, to protection from multiple autoimmune diseases including systemic lupus erythematosus (SLE) and multiple sclerosis (MS). The protective role of this SNP in autoimmune pathogenesis, however, remains incompletely understood. Here we found that T follicular helper (Tfh) cells, switched memory B cells, and IFNAR signaling were decreased in healthy individuals that expressed the protective variant TYK2A1104 (TYK2P). To study this variant in vivo, we developed a knock-in murine model of this allele. Murine Tyk2P expressing T cells homozygous for the protective allele, but not cells heterozygous for this change, manifest decreased IL-12 receptor signaling, important for Tfh lineage commitment. Further, homozygous Tyk2P T cells exhibited diminished in vitro Th1 skewing. Surprisingly, despite these signaling changes, in vivo formation of Tfh and GC B cells was unaffected in two models of T cell dependent immune responses and in two alternative SLE models. TYK2 is also activated downstream of IL-23 receptor engagement. Here, we found that Tyk2P expressing T cells had reduced IL-23 dependent signaling as well as a diminished ability to skew towards Th17 in vitro. Consistent with these findings, homozygous, but not heterozygous, Tyk2P mice were fully protected in a murine model of MS. Homozygous Tyk2P mice had reduced expansion of pathogenic CD4+ T cells in the draining lymph nodes (LN) as well as fewer infiltrating CD4+ T cells within the CNS. Most strikingly, homozygous mice had a decreased proportion of IL-17+/IFNγ+, double positive, pathogenic CD4+ T cells in both the LN and CNS. Thus, in an autoimmune model, such as EAE, impacted by both altered Th1 and Th17 signaling, the Tyk2P allele can effectively shield animals from disease. Taken together, our findings suggest that TYK2P diminishes IL-12, IL-23, and IFN I signaling and that its protective effect is most likely manifest in the setting of autoimmune triggers that concurrently dysregulate at least two of these important signaling cascades.